Biblioteka szkolna dla uczniów niesłyszących? metody i formy pracy na przykładzie ZespołuPlacówek Szkolno-Wychowawczych w Kielcach = The school library for deaf pupils: methods and forms of work,based on the example of the Special Education School-Complexin Kielce - Lewandowski, Albert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The aim of this article is to present the activities of the library of the Special Education School-Complex in Kielce, which, in the context of Kielce?s school libraries, exhibit a unique set of specific operational features. This not only concerns the opening hours - the library is open from Monday to Thursday, from 17 to 21 - but also the beneficiaries, who are students of state schools and children and young people with hearing impairments from the Special Education Centre. The first part of the article is devoted to general issues related to surdopedagogy: terminology and classification of concepts. In the next part the author characterizes the specificity of the Special Education School-Complex, presents basic dataabout the library and describes the program ?Books of our dreams?, implemented by the institution in the school year 2015/2016. The main part of the article concerns the methods and forms of work used in classes with children and teenagers with hearing impairments. These include competitions, library lessons, trips, art classes and various types of theatrical forms addressed to groups of students with such impairments. The author places great emphasis on working with traditional books. However, these does not entail omitting modern sources of information which, if used properly, can contribute to the dissemination of reading among children and youth.
Keywords: dziecko z niepełnosprawnością; głusi; biblioteki szkolne; młodzież szkolna; czytelnictwo; child with a disability; deaf; school libraries; school youth; reading